THE CAPABILITY APPROACH (CA) TO INCLUSIVE EDUCATION: INTEGRATION CULTURAL FACTORS IN THE EDUCATION OF PERSONS WITH DEVELOPMENTAL DISABILITIES AND DISABILITIES (Heritage, 2025)
The paper analyzes the application of the Capability Approach (CA) in the education of persons with developmental disabilities and disabilities. Using the method of content analysis of normative documents and scholarly works addressing the theoretical framework and implementation of the CA, the paper emphasizes the importance of implementing culturally competent practices for inclusion. The list of central capabilities aims to ensure a minimum threshold of dignity, freedom, and active participation in society for every individual, while social justice is based on the premise that each citizen possesses a sufficient level of basic capabilities, in accordance with the defined culture, history, and religion. It is essential to recognize how cultural values influence the development of key capabilities in education, which requires intercultural dialogue. In the context of Serbian culture, traditional values and cultural heritage can play a significant role in supporting inclusive education. Special attention is devoted to the role of traditional cultural forms, such as kolo and music therapy, as means of developing cognitive abilities, social skills, interpersonal connectedness, and a sense of belonging for persons with developmental disabilities and disabilities. Therefore, the paper highlights the need to preserve and integrate cultural resources into inclusive education as instruments for developing capabilities and fostering cultural identity, and as a prerequisite for combating multiple discrimination and achieving social justice.
Keywords: Capability Approach (CA), education of persons with developmental disabilities and disabilities, inclusion, culturally competent practice, Serbian cultural heritage, tradition, cultural identity, social justice